Power line communication technologies for smart grid applications: A review of advances and challenges - Yigit, Melike; Gungor, V. Cagri; Tuna, Gurkan; Rangoussi, Maria; Fadel, Etimad (Computer networks (Amsterdam, Netherlands : 1999), 2014)
This paper investigates the use of Power Line Communication (PLC) for Smart Grid (SG) applications. Firstly, an overview is done to define the characteristics of PLC and PLC-based SG applications are addressed to define the compatibility of PLC. Then, the advantages and disadvantages of PLC for SG applications are analyzed to improve the issues related to PLC. Due to the past standardization problem of PLC, new protocols and standards proposed for PLC are reviewed to see possible solutions toward its standardization. In addition, both completed and ongoing developments in the PLC technologies and their worldwide implementations are reviewed in this study. Finally, open research issues and future works are given.